Surgical treatment of small- and medium-sized primary macular holes with preservation of the internal limiting membrane in the papillomacular nerve fiber bundle area - N.M. Shilov; A.V. Tereshchenko; E.V. Erokhina; S.V. Novikov; A.A. Lugovaya; A.G. Kurguzova (РМЖ "Клиническая офтальмология")
N.M. Shilov1, A.V. Tereshchenko1,2, E.V. Erokhina1, S.V. Novikov1, A.A. Lugovaya3, A.G. Kurguzova4 1Kaluga Branch of the S. Fyodorov Eye Microsurgery Federal State Institution, Kaluga, Russian Federation 2K.E. Tsiolkovskiy Kaluga State University, Kaluga, Russian Federation 3Smolensk State Medical University, Smolensk, Russian Federation 4M.M. Krasnov Research Institute of Eye Diseases, Moscow, Russian Federation Aim: to develop a surgical technique for primary macular holes (MH) with preservation of the internal limiting membrane (ILM) in the projection of the papillomacular bundle (PMB) and to evaluate its clinical efficacy. Patients and Methods: forty-two patients (42 eyes) with primary small and medium-sized MH (minimum diameter <400 μm) were included. All patients underwent the proposed surgical technique with preservation of the PMB (keyhole surgery). ILM peeling was performed by sequential dosed removal of its local portions concentric to the MH. A 0.3-0.5-mm-wide belt-like intact foveolar ILM around the MH and intact ILM near the PMB were preserved. To close the MH, a monolayer ILM fragment was created (the upper inverted ILM fragment, which was covered and tamponaded over the MH). Results: anatomical closure of the MH was achieved in all patients. The preservation of the foveolar part of the ILM and its fragment in the projection of the PMB resulted in a high functional outcome, as evidenced by BCVA (20/25 at 12 months after surgery) and microperimetry, which showed an increase in retinal light sensitivity and disappearance of the absolute scotoma in the central fovea in all patients in the postoperative period. Spectral optical coherence tomography showed multiple defects of the inner retinal layers in the perifovea of varying severity, corresponding to the area of ILM peeling and not involving the papillomacular area. Conclusion: the proposed surgical technique for MH with preservation of PMB using keyhole surgery provides permanent closure of primary small and medium-sized MH and good functional results with minimal retinal damage during the surgical procedure. Keywords: macular hole, internal limiting membrane, papillomacular bundle. For citation: Shilov N.M., Tereshchenko A.V., Erokhina E.V., Novikov S.V., Lugovaya A.A., Kurguzova A.G. Surgical treatment of small- and medium-sized primary macular holes with preservation of the internal limiting membrane in the papillomacular nerve fiber bundle area. Russian Journal of Clinical Ophthalmology. 2024;24(3):109–115 (in Russ.). DOI: 10.32364/2311-7729-2024-24-3-2.